Circularly Polarized Luminescence of [6]Helicenes through Excited‐State Intramolecular Proton Transfer. Issue 4 (22nd March 2022) - Göbel, Dominik; Míguez‐Lago, Sandra; Ruedas‐Rama, Maria Jose; Orte, Angel; Campaña, Araceli G.; Juríček, Michal
Abstract: We present the concept of combining circularly polarized luminescence (CPL) and excited‐state intramolecular proton transfer (ESIPT) features into a single molecule as a strategy to generate high‐performance ESIPT‐based CPL materials. For this purpose, a [6]helicene bearing two ESIPT structural units was synthesized using a double Suzuki–Miyaura reaction and a double C(sp 2 )−H hydroxylation approach. The photophysical properties of the doubly hydroxylated [6]helicene were studied in parallel with a non‐hydroxylated [6]helicene control compound, revealing that the presence of a chiral [6]helicene unit results in a strong CPL response and the presence of the ESIPT units in a considerable red shift. The red‐shifted emission along with the outstanding g lum (≈10 −2 ) and a large Stokes shift makes the doubly hydroxylated [6]helicene a promising candidate for use in optoelectronics. Abstract :